Reexamining the Lecture Method in Learning: A Contemporary Pedagogical Perspective - Arditya Prayogi; Riki Nasrullah; Rohmad Abidin; Dimas Prasetya; Ryan Marina (RAM PUBLISHER, 2026)
Lectures are often perceived as a conventional teaching method that is less relevant to modern learning demands, which emphasize student participation. However, in educational practice, lectures are still widely used and have certain pedagogical functions that cannot be fully replaced by other methods. This article aims to conceptually examine the relevance of the lecture method as a learning method that is still widely used in various learning contexts, particularly within the framework of contemporary pedagogy. This article uses a literature review method with a qualitative-descriptive approach, through critical analysis of scientific literature, pedagogical books, and relevant research results that discuss lecture methods and modern learning. The results of the study show that lecture methods remain relevant when used proportionally, reflectively, and adaptively, especially for conveying conceptual frameworks, building initial learning orientation, and explaining abstract and systematic material. This relevance is even stronger when the lecture method is combined with interactive strategies, learning media, and the use of educational technology. The implications of this study emphasize the importance of repositioning the lecture method not as a single method, but as an integral part of a flexible and contextual learning strategy, so that it can support the achievement of learning objectives in a more meaningful way.